Obstetrical outcome in gestational diabetes mellitus: a retrospective study - Manjappa, Anitha Aldur; Menon, Maya; Patil, Aruna Bholenath (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Gestational diabetes mellitus (GDM) is associated with adverse maternal and fetal outcomes. Majority of the maternal complications associated with GDM have been decreasing nowadays, however the relative risk of development of perinatal complications remain higher in women with hyper glycaemia. Methods: This retrospective study was conducted among 286 delivered pregnant women. The pregnant women were diagnosed as GDM by DIPSI diagnostic criterion. The study was performed to find the association of various risk factors with GDM occurrence and to assess the obstetrical outcome in the GDM and normoglycaemic women. Results: Out of the 286 women, the proportion of women affected with GDM was 20.6%. The onset of GDM was more common among women between 25-30year (62.7%). GDM onset is increased when they had previous history of GDM and family history of diabetes. The obstetric complications were less common among GDM women (23.72%). GDM women had increased rate of caesarean delivery (69.5%) and induction of labour (42.4%). The neonatal complications were more common among GDM neonates (57.62%). The proportion of occurrence of congenital anomalies and macrosomia (>3.5kg) was similar among both groups. Conclusions: Risk factors associated with GDM onset such as previous history of GDM and family history of diabetes are significant risk factors. Advanced age, increasing parity and occurrence of abortions were not associated with GDM onset. With good glycaemic control the obstetrical complications and macrosomia are preventable. Rate of Induction of labour, caesarean delivery and neonatal morbidity remains higher among GDM women.